Amniotic Membrane Transplantation In Ocular Surface Disorders - Faiz Muhammad Halepota, Muhammad, Khalid Iqbal Talpur (Pakistan Journal of Ophthalmology, 2006)
We report our experience of amniotic membrane transplantation. Altogether eight cases were performed for different ocular surface disorders. Two cases of extensive symblepheron due to ocular cicatrical pemphigoid and acute epidermal toxic necrolysis. One each case of persistent epithelial defect due to Stevens- Johnson syndrome, Mooren's ulcer, shield ulcer in vernal keratoconjunctivitis, central corneal perforation following treated infective keratitis, conjunctival squamous cell carcinoma excision and Bowen's disease excision. All the cases were successful except one case of extensive symblepheron following epidermal toxic necrolysis, leading to detachment of amniotic membrane and perforation of cornea.